1993
DOI: 10.1007/bf00032962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper on shoot and root regeneration in wheat, triticale, rape and tobacco tissue cultures

Abstract: CuSO 4 (0.1-100 ~M) significantly enhanced shoot regeneration from calli of wheat and triticale and of tobacco leaf disc cultures. In cultures of wheat and triticale, CuSO 4 also stimulated root formation. When equal concentrations of CuSO 4 were applied in different media, it was found that the components of the basal media had only modifying effects. CuSO4 pretreatment promoted plant survival when regenerated wheat plants were transferred directly to potting soil. In contrast with CuSO4, AgNO 3, which also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 16 publications
5
48
0
2
Order By: Relevance
“…In the case of L. tegeleriana, however, BAP and NAA are used in the induction of axillary bud proliferation (see above). Increased CuSO 4 level has positive effect on regeneration if applied in callus cultures of wheat and other cereals (Purnhauser and Gyulai, 1993). Similarly to the results achieved in rapeseed by the same authors, our results did not confirm the positive effect of this treatment in L. tegeleriana either.…”
Section: Somatic Callus Cultures Of L Tegelerianasupporting
confidence: 37%
“…In the case of L. tegeleriana, however, BAP and NAA are used in the induction of axillary bud proliferation (see above). Increased CuSO 4 level has positive effect on regeneration if applied in callus cultures of wheat and other cereals (Purnhauser and Gyulai, 1993). Similarly to the results achieved in rapeseed by the same authors, our results did not confirm the positive effect of this treatment in L. tegeleriana either.…”
Section: Somatic Callus Cultures Of L Tegelerianasupporting
confidence: 37%
“…Previous studies have suggested that Cu enzymes could play an important role in plant tissue culture (Purnhauser, 1991;Purnhauser and Gyulai, 1993). Purnhauser (1991) examined the effects of six copper levels on regeneration from callus cultures in hexaploid wheat and found that regeneration rates were eight times higher on medium containing 10 µM CuSO 4 than on the original MS copper level (0.1 µM).…”
Section: Discussionmentioning
confidence: 99%
“…The silver ion is reported to be an inhibitor of ethylene action by competitively binding to ethylene receptors which are located predominantly at the intracellular membrane, while AVG inhibits ethylene biosynthesis directly (Vain et al, 1989;Zhang et al, 1998). In addition to silver ion, other heavy metals including Cu and other ethylene inhibitors (Co and Ni), also significantly facilitate the regeneration and somatic embryogenesis (Purnhauser & Gyulai, 1993;Roustan et al 1989). …”
Section: Chemical Additivesmentioning
confidence: 99%